PENGALAMAN KERJA, SKEPTISME PROFESIONAL, TEKANAN WAKTU DAN PENDETEKSI FRAUD (STUDI PADA BPKP JAWA TENGAH) - soenanto, joshua mitchel; Pesudo, David A. A. (Jurnal Ilmu Sosial dan Humaniora, 2020)
Abstract This purpose of the research is to determine the effect of work experience, professional skeptism, and time pressure on fraud detection in BPKP (Badan Pengawasan Keuangan dan Pembangunan), Central Java. This research is a quantitative descriptive study where the questionares is used as a research instrument. Saturated sampling technique is used in order to obtain 45 samples of internal auditor as respondents. Multiple Linear Analysis is used as analysis technique, includes : validity test, reability test, classic assumption test, hypothesis test. The result of this study indicate that work experience and professional skeptism has a significant positive effect on fraud detection, but time pressure has a negative significant effect on fraud detection in BPKP (Badan Pengawasan Keuangan dan Pembangunan), Central Java. Key words : Work experience, Professional Skeptism, Time Pressure, Fraud Detection